Fodder Value and Use of Bulbbar Barbar for Pure and Mixed Seeds with Catran Perfect Under Conditions of Adyr Of Uzbekistan - X. A, Kediyorov (International Journal of Psychosocial Rehabilitation, 2020)
When introducing into the culture of a wild fodder plant, it is necessary to study and characterize its forage advantages in detail. For this, first of all, it is necessary to study the chemical composition of the plant fodder mass, determine the amount of nutrient organic substances and their digestibility, silage, etc. only then can conclusions be drawn about the possibility and expediency of its use, introduction to culture.